HUBUNGAN KEBIASAAN MENONTON TELEVISI DENGAN OBESITAS PADA REMAJA DI SMA NEGERI 1 TOMBARIRI KABUPATEN MINAHASA - Bidjuni, Hendro; Kallo, Vandri (JURNAL KEPERAWATAN, 2018)
Abstract: Obesity is a disorder or disease that is characterized by excesstive accumulation of body fat in the body. Watching television is a habit that is often done by everyone but most people do not understand the correct way of watching television that does not interfere their health conditions. The purpose of this study was to determine the relation between the habit of watching television with obesity in adolescence age in Kabupaten Minahasa Kecamatan Tombariri 1st Senior High school. The research design is using retrospective approach. The sample of the study was 60 correspondents, devided into 30 correspondents as case group, and 30 correspondents as control group. The date that were collected using observation sheets of television viewing frequency and body mass index observation sheet. The results of the statitical chi square test relation betweeen the habit of wathing television with obesity 95%(Î±â‰¤0,05) and the results optained p value 0,004. The conclusion that there is a relation between the habit of watching television with obesity in adolescence in Kabupaten Minahasa Kecamatan Tombariri 1st Senior High School.Keywoards : The habit of watching television, obesity.Abstrak: Obesitas adalah suatu kelainan atau penyakit yang ditandai oleh penimbunan jaringan lemak dalam tubuh secara berlebihan. Menonton televisi adalah kebiasaan yang sering dilakukan oleh setiap orang tetapi sebagian besar orang tidak memahami bagaimana cara menonton televisi yang tidak akan merugikan kesehatan. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan kebiasaan menonton televisi dengan obesitas pada remaja di SMA Negeri 1 Tombariri Kabupaten Minahasa. Desain Penelitian yaitu menggunakan Deskriptif Analitik, dengan menggunakan pendekatan Retrospektif. Sampel sebanyak 60 responden dimana 30 responden sebagai kelompok Kasus dan 30 responden sebagai kelompok Kontrol. Data dikumpulkan dengan menggunakan lembar observasi frekuensi menonton televisi dan lembar observasi indeks massa tubuh. Hasil Uji Statistik Chi Square hubungan kebiasaan menonton televisi dengan obesitas 95% (Î±<0,05) dan hasil diperoleh p value 0,004. Kesimpulan yaitu terdapat hubungan antara kebiasaan menonton televisi dengan obesitas pada remaja di SMA Negeri 1 Tombariri Kabupaten Minahasa.Kata Kunci : Kebiasaan menonton televisi, obesitas.